(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The quality of warranties is appreciated based on the extent to which these warranties can cover the credit, as well as on their nature and legal character. Depending on the nature of the warranties, each bank takes into account their own percentages in appreciating the value of the warranties, according to their own crediting rules. This has resulted in a distortion of the value of the goods used as warranty, as each bank, depending on its own crediting policy, would under-valuate or over-valuate the value of the spinoffs. The purpose of credit analysis is to avoid profit losses or business losses caused by bad debts, that is, by granting credits to customers who don’t pay off the loan or by failing to grant credits to potentially good customers.